Eco-Khan Palace / Muhammad Farkhan Idzahar - Idzahar, Muhammad Farkhan (2021)
Eco-Khan Palace is a plant nursery that provide variety of beautiful plants that suits customer satisfaction. Our business strives to meet customer satisfaction by offering to our customer a high-quality plant with a good customer service. Our plant nursery was founded on year 2021 by an enthusiastic man who love nature and gardening, which is Muhammad Farkhan Bin Idzahar. Eco- Khan Palace was established in Shah Alam, Selangor by our founder from a humble beginning on a small piece of land. We provide a wide range of high-quality landscape plants ranging from potted plants, bonsai, turfing, fruits planting materials, landscape accessory supplies, landscaping & garden design Our target audience is a group of people who are passionate in gardening and nature, and the people that are looking for the high-quality plants with affordable prices. As a local plant nursery, Eco-Khan Palace have decided to make its present known and visible by creating a Facebook Page namely “Eco-Khan Palace” and make a business registration on Go- Ecommerce.